Coordination and matching of tire system of new straddle-type rapid transit vehicle. Issue 2 (1st February 2023) - Wu, Haoxin; Du, Zixue; Yang, Zhen; Wen, Xiaoxia; Xu, Zhouzhou; Xin, Liang
Abstract : Under the trend of promoting economy, environmental protection and high efficiency in the urban rail transit industry, this paper proposes a new type of straddle-type rapid transit system. Compared with most straddle-type monorail systems, it has the advantages of low construction cost and low operating cost, which makes it more suitable for urban rail transit system in small and medium-sized cities. In the process of vehicle development and design, in order to achieve the coordination and matching of tire systems and reduce the wear of tire systems, this work uses a multi-objective optimisation method to reduce the guiding torque of each tire system when the vehicle passes through the curve. Based on the vehicle dynamics model, the multi-body dynamics simulation model of the vehicle is established. The guiding torque of each tire system is taken as the optimisation objective, and the position and dynamic parameters of each tire system are taken as the optimisation parameter. Based on the NSGA-II algorithm, the ISIGHT and SIMPACK software are used for co-simulation. Finally, the guiding torque of each tire system is effectively reduced, and the coordination and matching of tire system is realised.